1998
DOI: 10.1103/physrevd.58.123507
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic oscillations and viscosity

Abstract: Using a simple thermo-hydrodynamic model that respects relativistic causality, we revisit the analysis of qualitative features of acoustic oscillations in the photon-baryon fluid. The growing photon mean free path introduces transient effects that can be modelled by the causal generalization of relativistic Navier-Stokes-Fourier theory. Causal thermodynamics provides a more satisfactory hydrodynamic approximation to kinetic theory than the quasi-stationary (and non-causal) approximations arising from standard … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
148
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(152 citation statements)
references
References 35 publications
4
148
0
Order By: Relevance
“…If we choose the fundamental 4-velocity u µ such that σ µν = 0, which is the covariant analogue of the longitudinal or conformal Newtonian gauge in metric-based perturbation theory (see [19,20] for further discussion), then the shear propagation equation (51) becomes a constraint determining the brane tidal tensor:…”
Section: Cosmological Scalar Perturbationsmentioning
confidence: 99%
“…If we choose the fundamental 4-velocity u µ such that σ µν = 0, which is the covariant analogue of the longitudinal or conformal Newtonian gauge in metric-based perturbation theory (see [19,20] for further discussion), then the shear propagation equation (51) becomes a constraint determining the brane tidal tensor:…”
Section: Cosmological Scalar Perturbationsmentioning
confidence: 99%
“…Despite there being no proper Newtonian limit for GR on cosmological scales, recent works on so-called quasi-Newtonian cosmologies [18][19][20] have shown that gravitational physics (such as analysis of nonlinear collapse and structure formation using the Zel'Dovich approximation 21 ) can be studied to a good approximation using such an approach. In, 18 it was shown that non-linear quasi-Newtonian cosmologies are generally covariantly inconsistent in General Relativity.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the ansatz for the evolution of the gravitational potential introduced by van Elst and Ellis 18 and Maartens' generalisation, 19 we first consider what happens if we modify the stress-energy tensor to include a a general anisotropic stress π ab and extend the general relativistic integrability conditions for the linearized models about the FLRW background. We show that while a general anisotropic source does not lead to integrability conditions that close on time propagation, f (R) gravity is special because of the particular form π ab takes in this case.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations